Structural and catalytic properties of a novel vanadium containing solid core mesoporous silica shell catalysts for gas phase oxidation reaction - Venkatathri, N.; Pillai, Vijayamohanan K.; Rajini, A.; Raju, M. Nooka; Reddy, I. A. K. (Journal of Chemical Sciences, 2013)
A novel vanadium containing solid core mesoporous silica shell catalyst was synthesized with different Si/V ratios by sol-gel method under neutral conditions. The synthesized materials were characterized by various techniques and gas phase diphenyl methane oxidation reaction. The mesoporosity combined with microporosity are formed by incorporation of octadecyltrichloro silane and triethylamine in the catalyst and it was found out from E-DAX and BET-surface area analysis. The material was found to be nanocrystalline. Vanadium is present as V4 + species in as-synthesized samples and convert to V5 + on calcination. Most of the vanadium is present in tetrahedral or square pyramidal environment. Incorporation of vanadium in silica framework was confirmed by Si-29 MAS NMR analysis. Among the various vanadium containing solid core mesoporous silica shell catalysts, the Si/V = 100 ratio exhibited maximum efficiency towards diphenyl methane to benzophenone gas phase reaction. The optimum condition required for maximum conversion and selectivity was found out from the catalytic studies.
Keywords: diphenylmethane; Gas phase oxidation; vanadium containing solid core mesoporous silica shell